Pengaruh Dosis Minyak Cengkeh Terhadap Populasi Hama Callosobruchus chinensis L., Viabilitas Dan Vigor Benih Dua Kultivar Kacang Hijau Setelah Periode Simpan Tiga Bulan - Siti Syarah Nurbaekah; Sumadi Sumadi; Anne Nuraini (Agrologia, 2018)
Callosobruchus chinensis L. still become the primary pest of mung bean, it can cause damage until 70 percent. Pest control on mung bean seeds can be done by using anorganic protectant and bio protectant. The aim of the research was to determine the dosage of clove oil that could suppressed the population of weevil C. chinensis L. and maintaining seed viability and seed vigor of two mung bean cultivar after three months storage. The experimental design was Completely Randomized Design with 10 treatments combination of cultivar and clove oil dosage; all treatment were replicated three times. The mungbean seeds were cultivar Vima 1 and Vima 3.  The clove oil dosages used were 0 mL kg-1, 0,5 mL kg-1, 1,0 mL kg-1, 1,5 mL kg-1 and 2,0 mL kg-1. The mungbean result of experiment showed that there were significant effect between cultivar and clove oil dosage on germination rate percentage after three months storage, but no significant effect on weevil population and vigor index. The dosage of 1,5 mL kg-1 clove oil was the better treatment to maintaining seed viabilty andits vigor.Keywords: Mung bean, C. chinensis L., Clove oil, Seed viability and Seed Vigor.